INTERNET SEARCH TRAFFIC AND ITS INFLUENCE ON LIQUIDITY AND RETURNS OF INDONESIA STOCKS: AN EMPIRICAL STUDY - Usman, Berto; Tandelilin, Eduardus (Journal of Indonesian Economy and Business, 2014)
The development of advanced information technology has become a standard in the processof improving corporate value. This is seen through the high level of investorsâ awareness of thebrand and information that company holds (Da, Engleberg, and Gao, 2011; Bank, Larch, andGeorge, 2011; Joseph, Wintoki, and Zhang, 2011). Among the information providers, internetplays an important role not only in accessing information, but also as a medium that can beapplied to publish a wide range of financial reports or news to attract investors. This study aimsto examine the effect of investorsâ attention towards returns, liquidity and volatility of stockreturns. The results indicate that investorsâ attention which is represented by Google Insightcontributes positively and significantly to the explanation of returns, liquidity, and volatility ofstock returns in Indonesian manufacturing firms. Also, the phenomenon of informationtechnology usage can be one of the considerations for investors in order to discover what typesof companyâs criterion that is appropriate to be included in their investment portfolio.Keywords: investorsâ attention, returns, liquidity, volatility of stock returns